New Advances in Forming Functional Ceramics for Micro Devices - Dorey, Robert A.; Rocks, Sophie A.; Dauchy, Florent; Navarro, A. (Cranfield University, 2006)
Micro electromechanical systems (MEMS) are finding uses in an increasing number of diverse applications. Currently the fabrication techniques used to produce such MEMS devices are primarily based on 2-D processing of thin films. The challenges faced by producing more complex structures (e.g. high aspect ratio, spans, and multi-material structures) require the development of new processing techniques. Potential solutions to these challenges based on low temperature processing of functional ceramics, selective chemical patterning, and micro-moulding are presented to show that it is possible to create complex functional ceramic structures which incorporate non-ceramic conducting and support structures. The capabilities of both techniques are compared and the relative advantages of each explored.
Keywords: PZT; MEMS; microsystems